Heatwaves mortality according to specific causes in Argentinian cities (2005-2019) - Chesini, Francisco (2025)
Introduction: Heatwaves pose a significant natural threat to human health, with varying impacts on morbidity and mortality. Materials and methods: This study aimed to characterize the risk of mortality associated with heatwaves (HWs), considering specific causes of death in 21 Argentine cities between 2005 and 2019. An ecological observational epidemiological study was conducted using a time series statistical approach, with generalized additive models. Data were sourced from the Ministry of Health and the National Meteorological Service (NMS). Deaths due to cardiovascular (ICD10: I00-I99), respiratory (J00-J99), and renal (N00-N99) causes during HWs and their temporal lags were analyzed. Results: In 15 of the 21 cities, a significant increase in mortality was observed for the specific causes analyzed (cardiovascular: 13; respiratory: 10; and renal: 7) during HWs and their lags. Mortality increases were recorded in all regions, including Patagonia, where they were observed in two cities. Conclusions: The findings of this study will contribute to the development of more effective health promotion and protection policies.